Understanding the female athlete: molecular mechanisms underpinning menstrual phase differences in exercise metabolism - Oosthuyse, T.; Strauss, J. A.; Hackney, A. C. (European Journal of Applied Physiology, 2023)
Research should equitably reflect responses in men and women. Including women in research, however, necessitates an understanding of the ovarian hormones and menstrual phase variations in both cellular and systems physiology. This review outlines recent advances in the multiplicity of ovarian hormone molecular signaling that elucidates the mechanisms for menstrual phase variability in exercise metabolism. The prominent endogenous estrogen, 17-ß-estradiol (E2), molecular structure is bioactive in stabilizing plasma membranes and quenching free radicals and both E2 and progesterone (P4) promote the expression of antioxidant enzymes attenuating exercise-induced muscle damage in the late follicular (LF) and mid-luteal (ML) phases. E2 and P4 bind nuclear hormone receptors and membrane-bound receptors to regulate gene expression directly or indirectly, which importantly includes cross-regulated expression of their own receptors. Activation of membrane-bound receptors also regulates kinases causing rapid cellular responses. Careful analysis of these signaling pathways explains menstrual phase-specific differences. Namely, E2-promoted plasma glucose uptake during exercise, via GLUT4 expression and kinases, is nullified by E2-dominant suppression of gluconeogenic gene expression in LF and ML phases, ameliorated by carbohydrate ingestion. E2 signaling maximizes fat oxidation capacity in LF and ML phases, pending low-moderate exercise intensities, restricted nutrient availability, and high E2:P4 ratios. P4 increases protein catabolism during the luteal phase by indeterminate mechanisms. Satellite cell function supported by E2-targeted gene expression is countered by P4, explaining greater muscle strengthening from follicular phase-based training. In totality, this integrative review provides causative effects, supported by meta-analyses for quantitative actuality, highlighting research opportunities and evidence-based relevance for female athletes.